The Influence of Role Play Method by Hand Puppet Media in Speaking Class of Santo Rafael Kindergarten’s Students - Ridayanti, Putu Windi; Marleni, Kadek Devy; Ratnadi, Ni Nyoman Ari (Yavana Bhasha : Journal of English Language Education, 2021)
This study aimed at investigating whether the implementation of hand puppet in role play gave a significant effect to the students’ speaking competency. Hand puppets are dolls that are used as media or tools used in learning activities. Types of puppets that are usually used are hand puppets made of pieces of cloth. Methods: The research design used a pre-experimental design with a one group pre-posttest design. The populations used in this study were children in B group class in Santo Rafael Singaraja. The speaking measurement used an observation sheet in which it guided by a task. The sample size used is 30 respondents who have been selected using a total sampling technique. This study used parametric statistics using Paired Sample T-test with a significant level of α = 0.05. Results: The results showed that the pre-test mean was 56.00, and the post-test mean was 68.33. The results of parametric statistical tests using the Paired Sample T-test showed pre and post results (0.000) <α (0.05), which means that H0 is rejected and Ha is accepted. Conclusion: This shows that there is an influence of the role-play method by hand puppet media in speaking class of Santo Rafael Kindergarten Students.